Equivalent circuit representation and analysis of galloping-based wind energy harvesting - Tang, Lihua (2014)
Small-scale wind energy can be harvested for wireless sensing applications by exploiting the galloping phenomenon of a bluff body attached to a piezoelectric cantilever. Certain predictive model is required to understand the behavior of such a galloping-based piezoelectric energy harvester (GPEH). Conventional analytical and numerical models have simplified the interface circuit as a pure resistor. In practice, the energy generated by the harvester should be rectified before delivery to a real application. In such a case, the formulation of analytical or numerical model becomes cumbersome considering the complex coupling between the structure, fluid, piezoelectric transducer and practical interface circuit. This paper proposes an equivalent circuit representation approach to predict the performance of GPEHs, capable of incorporating various interface circuits. The mechanical parameters and piezoelectric coupling in the system are represented by standard electronic components and the aerodynamic force by a user-defined component (non-standard). The entire system is modeled in a circuit simulator for system-level simulation and evaluation. The proposed approach is verified by theoretical solution and experiment. Subsequent parametric study is performed to investigate the influence of standard AC and DC interfaces on the GPEH’s behavior, with a focus on the threshold of galloping, power output and induced electrical damping.